Determinants of consumer attitudes toward mobile advertising: a cross-border study between Malaysia and Indonesia using PLS-MGA - Mohamed Ghazali, Raimi Nur Hakimi; Lim, Xin Jean; Cheah, Jun Hwa; Ting, Hiram; Soebandhi, Santirianingrum; Sudiyanti Sudiyanti; Kamal Basha, Norazlyn (Faculty of Economics and Management, Universiti Putra Malaysia, 2019)
Technological advancement has led to new models of marketing strategies which is mobile advertising to better reach consumers. However, despite the prevalence of mobile advertising and the ubiquitous use of mobile devices to develop markets, little has been done to examine the perceived value and attitude towards mobile advertising. The purpose of this study was to understand and compare the factors that influence perceived value and attitude towards mobile advertising between two countries in Southeast Asia, namely, Malaysia and Indonesia. A total of 300 questionnaires were evenly distributed among university students in Malaysia (150 samples) and Indonesia (150 samples). PLS-SEM based software (Smart PLS 3.0) was used to perform the path modelling and multi-group analyses. The findings showed that while information and entertainment are what Malaysians look for in mobile advertising, information was significantly more important to Indonesians. Although both agreed on the credibility and irritation part of advertisement, Malaysians seemed to value mobile advertising more than Indonesians. The implications of research are provided.